Athabasca Bridge Opening with Calling Lake First Nations - 02 - (Author); (Interviewer); (Publisher) (1952)
Photograph - Calling Lake First Nations people at the Athabasca Bridge Opening ceremonies in Athabasca, Alberta. June 9, 1952